Casa de leitura Thiago de Mello em Manaus - Queiroz, Flaviano Lima de (Universidade Federal do Amazonas, 2018)
This paper describes the method used to build the memorial of the poet Thiago de Mello, commissioned by the Ministry of Culture with the aim of providing the personal collection of the poet to the general public, through the Program More Culture. Within the Federal University of Amazonas the public will have access to different works of the author and other works acquired by him throughout his life as books, magazines, newspaper clippings, original design of the house of James, works of arts and letters personal poet. The collection will be distributed in three major themes developed by the poet, the man the forest and Latin America will be available at the Center for Culture Thiago de Mello in the city of Manaus.